2011
DOI: 10.1108/rjta-15-03-2011-b001
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Wool Fabric Dyed with Natural Dyes

Abstract: Natural dyes extracted from Cassia fistula and onion peels are used to dye wool that is pretreated with chitosan by using tannic acid as a mordant. The effect of the mordant concentration on the color strength (K/S) is discussed. The results obtained indicated that K/S increases after treatment with chitosan. It is also noticed that K/S increases with an increasing concentration of chitosan. K/S also increases with an increase of mordant concentration until 4% and then decreases. The effect of the dye bath pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Chitosan molecules in bacteria surrounds might complex metals and blockage some essential nutrients to flow, contributing to cell death [18][19][20].The positive charge on the N atom of, chitosan below pH 5.0 is more soluble and has a better antimicrobial activity by interfering with the negatively charged residues of macromolecules exposed on the fungal cell surface, and thereby changes the permeability of the plasma membrane.. It is found that the pretreatment with nanochitosan, effectively enhanced the antimicrobial activity due to large effective surface area [21][22][23][24].…”
Section: Surface Morphologymentioning
confidence: 99%
“…Chitosan molecules in bacteria surrounds might complex metals and blockage some essential nutrients to flow, contributing to cell death [18][19][20].The positive charge on the N atom of, chitosan below pH 5.0 is more soluble and has a better antimicrobial activity by interfering with the negatively charged residues of macromolecules exposed on the fungal cell surface, and thereby changes the permeability of the plasma membrane.. It is found that the pretreatment with nanochitosan, effectively enhanced the antimicrobial activity due to large effective surface area [21][22][23][24].…”
Section: Surface Morphologymentioning
confidence: 99%
“…This dye is being used extensively in dyeing of textile materials. Pharmacological studies have demonstrated that catechu is used in traditional medicines, show antiinflammatory and anticancer activities [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…But now a day's considerable research work is started throughout the world on the application of natural dyes [9]. Added to this natural dyes are gaining popularity as UV protective and antimicrobial clothing dyes [10]. family Fabaceae.…”
Section: Introductionmentioning
confidence: 99%